On the rare neotropical genus ophionthus bernhauer (Coleoptera: Staphylinidae: Staphylininae): Redescription of the type species and description of a new species - Rodríguez Melgarejo, Maryzender Erceliz (2021)
Two female specimens of the Neotropical genus Ophionthus Bernhauer were found during museum collection surveys, representing different species of the genus. These species are Ophionthus serpentinus Bernhauer, 1908 and O. asenjoi sp. nov. The genus Ophionthus was monotypic until the present study and only known from a single male specimen from Central Peru. The genus is redescribed with the inclusion of female characters from both the type species and the new species here proposed. Additionally, the systematic position of Ophionthus within the Neotropical lineage of Philonthina and its geographical distribution in Peru are reassessed. Descriptions, diagnoses, illustrations, pictures, a cladogram, and a distribution map are provided.